Determinan Yang Mempengaruhi Penyaluran Pembiayaan Gadai (Rahn) Pada PT. Pegadaian Syariah Indonesia Periode 2017-2021 - Reni Febriani; Moh. Huzaini; Taufiq Chaidir (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
This study aims to analyze the influence of determinants that influence the distribution of pawn financing (Rahn) at PT. Indonesian Sharia Pawnshop for the 2017-2021 Period. The data used is quarterly data for each variable. The method used in this research is the multiple linear regression method using the Ordinary Least Square (OLS) analysis tool through the Eviews 9 program. The research results obtained are a) From the t test, the results show that partially the variables Number of Customers and Gold Price have a significant influence towards the Distribution of Pawn Financing (Rahn). Meanwhile, the Inflation Rate variable does not have a significant influence on the Distribution of Pawn Financing (Rahn); b) From the results of the f test, it was found that simultaneously the variables Number of Customers, Inflation Level and Gold Prices had a significant influence on the Distribution of Pawn Financing (Rahn); c) From the Adjusted R2 test, the results show that the variables Number of Customers, Inflation Level and Gold Price have an influence of 95.1% on the Distribution of Pawn Financing (Rahn)